Latent class analysis of the association between polycyclic aromatic hydrocarbon exposures and body mass index. (December 2018) - Hendryx, Michael; Luo, Juhua
Abstract: Background: People experience multiple co-occurring exposures to environmental pollutants, but analyses of multiple exposures have rarely been reported. Objectives: We used latent class analysis to estimate co-exposures to multiple polycyclic aromatic hydrocarbons (PAH), and tested the associations of latent classes to body mass index. Methods: We analyzed National Health and Nutrition Examination Survey (NHANES) 2013–2014 data. The sample included 2354 people aged 6–80 years. Measures included seven urinary PAH metabolites, BMI, and demographic and behavioral covariates. People were classified into mutually exclusive latent classes characterized by unique profiles of multiple PAH exposures. These classes were used as categorical independent variables in weighted multiple regression models with BMI as the dependent measure. Models were analyzed overall and by age groups (6–19, 20–59, and 60 and over.) We compared results using latent classes to results using a summed PAH exposure measure. Results: Five latent classes were identified. Two of these classes were significantly associated with higher BMI overall (p < .0001) and for the two youngest age groups. One of these classes was characterized by high multiple exposures across all PAHs, and one by moderate exposures but relatively high naphthalene and phenanthrene. The summed PAH score was associated with higher BMI only for the youngest age group. Conclusions: Persons experience multiple co-exposures to PAHs that are related to BMI and obesity across age groups. Latent class analysis provides information on higher order interactions among multiple chemicals that a summed score does not. Future work may apply this approach to other outcomes or types of co-exposures. Highlights: Latent class analysis identified patterns of multiple co-occurring exposures to polycyclic aromatic hydrocarbons. Five latent classes were identified characterized by unique exposure profiles. Two classes representing multiple co-exposures were associated with higher body mass index in children and adults. Latent class analysis provides a possible method for the study of multiple co-occurring environmental exposures.